Criticism and truth - Barthes, Roland (Continuum, 2004)
Roland Barthes (1915-1980) was a major French writer, literary theorist and critic of French culture and society. His classic works include Mythologies and Camera Lucida. Criticism and Truth is a brilliant discussion of the language of literary criticism and a key work in the Barthes canon. It is a cultural, linguistic and intellectual challenge to those who believe in the clarity, flexibility and neutrality of language, couched in Barthes' own inimitable and provocative style. Translated and Edited by Katrine Pilcher Keuneman Introduced by Philip Thody.